1993
DOI: 10.1111/j.1365-2761.1993.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus cyprini: a search for viral genome in infected fish by infected fish by in situ hybridization

Abstract: Abstract. Herpesvirus cyprini (CHV) genome was traced in carp, Cyprinus carpio L., after acute infection by the method of in situ hybridization with biotinylated probes. The viral genome was detected in several tissues including cranial nerve ganglia. Subcutaneous tissue and spinal nerves. However, at this stage, viral antigens were not detected and the virus was not isolated. The viral genome was also detected in the same fish tissues when papillomas were present which contained viral antigens and even infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 6 publications
(8 reference statements)
0
45
0
Order By: Relevance
“…For instance, latent CyHV-1 persists in carp that survive infection (41), and AngHV-1 persists in surviving infected eels (38,47). In these cases, the viral genome was found in cranial nerve cells and spinal nerves by using in situ hybridization (31,41,42). It would be interesting to determine whether the pathogenic and attenuated CNGV and CyHV-2 also persist in nerves of survivors.…”
Section: Latencymentioning
confidence: 99%
“…For instance, latent CyHV-1 persists in carp that survive infection (41), and AngHV-1 persists in surviving infected eels (38,47). In these cases, the viral genome was found in cranial nerve cells and spinal nerves by using in situ hybridization (31,41,42). It would be interesting to determine whether the pathogenic and attenuated CNGV and CyHV-2 also persist in nerves of survivors.…”
Section: Latencymentioning
confidence: 99%
“…The best evidence comes from studies of the Lucké tumor, in which RaHV1 nucleic acid and proteins have been demonstrated in non-infectious, virus-free tumor tissue that, upon temperature manipulation, can yield infectious virus (Biggs 1972, Naegele & Granoff 1980, Tweedell 1989. Moreover, evidence for a long-term carrier state, which may or may not involve latency, has been described in several fish HVs, including IcHV1 (Wise et al 1985, Boyle & Blackwell 1991, Baek & Boyle 1996, Gray et al 1999, Thompson et al 2005, SalHV2 (Gou et al 1991, Kimura & Yoshimizu 1998), CyHV1 (Sano et al 1993), AngHV1 (van Nieuwstadt et al 2001, Shih 2004, and CyHV3 (Adkison et al 2005, Bercovier et al 2005, St-Hilaire et al 2005. These reports, and others of an anecdotal nature, indicate the existence of long-term infections (perhaps latency) caused by a wide selection of viruses in the family Alloherpesviridae.…”
Section: Discussionmentioning
confidence: 99%
“…Such papillomas coalesce as they spread over the surface of carp as white plaques, and develop focal exophytic masses (Wildgoose, 1992). These papillomas are caused by Herpesvirus cyprini (also cyprinid herpesvirus 1, CHV) (Sano et al, 1991), regress in warm summers or when held above 20°C (Sano et al, 1993b), and persist below 15°C (Sano et al, 1993a). Viruses have also been associated with papillary epidermal plaques in other fish species (Wolf, 1988), such as walleye, in which a retroviral etiology is suspected (LaPierre et al, 1998).…”
Section: Beckwith Et Almentioning
confidence: 99%